From Cultural Sustainability to Culture of Sustainability: Preservation of Games in the Context of Digital Materiality - Garda Maria; Nylund Niklas; Sivula Anna; Suominen Jaakko (Finland, 2022)
In this paper, we set out to explore some of the most prevalent questions regarding cultural sustainability in the context of preservation of digital games. Since the 1980s, the concept of sustainable development has been successively expanded to incorporate not only environmental and economic aspects but also the social and cultural, as well as relating to values such as human rights and broadly understood equality (Stylianou- Lambert et al. 2014). We would like to examine what kind of issues and considerations should be taken into account while developing a holistic approach to game preservation that also supports a culture of sustainability focused on broadly understood game heritage. What kind of unique challenges do game cultures and ludic artefacts present in this context? In our paper, we will look at a national case study of Finland where innovative and progressive approaches are currently being developed.
DiGRA ’20 : Proceedings of the 2020 DiGRA International Conference: Play Everywhere